﻿The history and typification of Lilium brownii A.Lemoinier (Liliaceae) - James A. Compton (PhytoKeys, 2022)
The Chinese Lilium brownii has been much confused with the Japanese endemic species Lilium japonicum. In this paper, it is shown that L. brownii was introduced to England at least four times between 1804 and 1819. The history of L. brownii is fully discussed and its taxonomy, nomenclature and relationships are examined. A neotype is designated for the name, its correct botanical authority is given and the correct place of its publication is provided. Lectotypes are also provided for the names Lilium aduncum Stapf, Lilium australe Stapf, Lilium odorum Planch., Lilium brownii var. colchesteri E.H.Wilson and Lilium brownii var. ferum Stapf.